How Do Social Media, Social Environment, and Trust in Government Influence Tax Compliance Intentions Among Generation Z? Exploring the Mediating Role of Tax Morality and Social Media Engagement - Ongkodjojo, Athena; Firmansyah, Helena Setiawati; Sadjiarto, Arja (International Economic Conference of Business and Accounting, 2025)
This study investigates the impact of social media, social environment, and trust in government on tax compliance intentions among Generation Z, with tax morality and social media engagement as mediating variables. Conducted in April 2025, the research utilized a quantitative approach through multiple linear regression, involving 230 active social media users from Generation Z. The findings reveal that social media positively influences tax compliance intentions, while social environment and trust in government do not have a significant effect. Mediation analysis indicates that tax morality enhances the relationship between social media and tax compliance intentions, whereas social media engagement does not serve as a mediator. These results aim to inform the development of tax policies that cater to the unique characteristics and behaviors of Generation Z. Consequently, tax authorities are encouraged to adopt more effective communication strategies via social media to foster tax compliance intentions among this demographic.